Thermal and hydrothermal influence of rapakivi igneous activity on late-Svecofennian granites in southeastern Finland. - Villar, Arturo (fi=Turun yliopisto|en=University of Turku|, 2017)
The recent discovery of polymetallic vein mineralizations around the Sarvlaxviken Bay (west-ernmost part of the Wiborg Batholith, SE Finland) has challenged the common assumption that Finnish rapakivi granites are metal-infertile and encouraged further exploration activities in the area. New discoveries have been made since then, including an ore boulder with a Zn-rich grei-sen alteration zone. Subsequent geochemical data of glacial till have revealed high metal con-centrations northwest of the ore boulder (south of Lake Lillträsket), where the bedrock is part of the Svecofennian domain, close to the Wiborg Batholith. The present study reviews the geologi-cal features of the Svecofennian rocks to locate the source of the ore boulder and evaluate the ore potential of these rocks. Two study areas were used for this project. The first one comprises a roughly 1 km2 large zone south of Lake Lillträsket, while the second one covers an E-W profile that spans from Lillträsket to 16 km into the west. These two study areas were defined to find evidence of alteration on a local and a regional level respectively. The examination of thin sections revealed K-feldspar transformations in the Svecofennian rocks, from a low thermal state (microcline) to a high thermal state (orthoclase). This disturb-ance, caused by the thermal effect of the rapakivi magmatism, is also reflected by strong read-justments in the isotopic system of four samples of the Svecofennian granite, as they yielded rapakivi (c. 1.6-1.4 Ga) Rb-Sr ages. Field observations and whole-rock geochemistry show that the bedrock in both study areas was originally composed of late-orogenic Svecofennian granites. However, the bedrock in the Lillträsket area displays an intense red coloration (produced by Fe oxides) around quartz veins and intertwined fractures as opposed to the whitish tone of the late-orogenic granites elsewhere. This feature is coupled with signs of K-metasomatism and higher contents of Fe, Rb, Th, Ti, Zr, Hf, Y, Zn, Be, Sc and Ag in the reddened granite. Numerous glacial till samples have been collected in the area of Lillträsket, for which geochem-ical data show high contents of Fe, Hf, Rb, Th, Y, Zr, As, Be, Cu, In, Li, Mo, Sn, W and Zn. The magnetic susceptibility and the Fe contents in the glacial till match with the ground magnetic features of the bedrock, indicating that these anomalies are extremely local. The evidence obtained in this project indicates that the rapakivi igneous activity had a signifi-cant impact in the Svecofennian granites, especially in the Lillträsket area, where hydrothermal alteration processes took place. It is suggested that the infiltrating fluid, responsible for such alteration, has a rapakivi origin and that the metal anomalies found in the Lillträsket area are linked to the mineralized systems of the Sarvlaxviken area.